Haplotype Variations and Evolutionary Analysis of the Granule-Bound Starch Synthase I Gene in the Korean World Rice Collection - Maung, Thant Zin; Yoo, Ji-Min; Chu, Sang-Ho; Kim, Kyu-Won; Chung, Ill-Min; Park, Yong-Jin (Frontiers in Plant Science, 2021)
Granule-bound starch synthase I (GBSSI) is responsible for Waxy gene encoding the, which is involved in the amylose synthesis step of starch biosynthesis. We investigated the genotypic and haplotypic variations of GBSSI (Os06g0133000) gene, including its evolutionary relatedness in the nucleotide sequence level using single-nucleotide polymorphisms (SNPs), indels, and structural variations (SVs) from 475 Korean World Rice Collection (KRICE_CORE), which comprised 54 wild rice and 421 cultivated represented by 6 ecotypes (temperate japonica, indica, tropical japonica, aus, aromatic, and admixture) or in another way by 3 varietal types (landrace, weedy, and bred). The results revealed that 27 of 59 haplotypes indicated a total of 12 functional SNPs (fSNPs), identifying 9 novel fSNPs. According to the identified novel fSNPs, we classified the entire rice collection into three groups: cultivated, wild, and mixed (cultivated and wild) rice. Five novel fSNPs were localized in wild rice: four G/A fSNPs in exons 2, 9, and 12 and one T/C fSNP in exon 13. We also identified the three previously reported fSNPs, namely, a G/A fSNP (exon 4), an A/C fSNP (exon 6), and a C/T fSNP (exon 10), which were observed only in cultivated rice, whereas an A/G fSNP (exon 4) was observed exclusively in wild rice. All-against-all comparison of four varietal types or six ecotypes of cultivated rice with wild rice showed that the GBSSI diversity was higher only in wild rice (π = 0.0056). The diversity reduction in cultivated rice can be useful to encompass the origin of this gene GBSSI during its evolution. Significant deviations of positive (wild and indica under balancing selection) and negative (temperate and tropical japonica under purifying selection) Tajima's D values from a neutral model can be informative about the selective sweeps of GBSSI genome insights. Despite the estimation of the differences in population structure and principal component analysis (PCA) between wild and subdivided cultivated subgroups, an inbreeding effect was quantified by FST statistic, signifying the genetic relatedness of GBSSI. Our findings of a novel wild fSNPS can be applicable for future breeding of waxy rice varieties. Furthermore, the signatures of selective sweep can also be of informative into further deeper insights during domestication.